The Effectiveness Of A Nutritional Education-Based Module For Pregnant Women In Preventing Stunting - Sriwiyanti; Nazarena, Yunita; Meilina, Ayu (Journal of Applied Nursing and Health, 2023)
Background: Maternal intake, especially during pregnancy, is one factor that plays an important role. Improvement of nutrition and health of pregnant women is closely related to the level of education, knowledge, and attitudes in meeting nutritional needs during pregnancy. Explain the Effectiveness of the Module for Pregnant Women based on Nutrition education, Nutritional Status, Knowledge, and attitudes of Pregnant Women in efforts to prevent stunting. Methods: The research design is pre-experimental with one group pre-test and post-test. They are held at one of the Puskesmas in Palembang from June to September 2023. Sampel is pregnant women with inclusion criteria, measuring nutritional status, knowledge, and attitudes of pregnant women before and after intervention with the Pregnant Women Module. Probability sampling variables and research variables of knowledge level, attitude, and nutritional status. The instruments used are questionnaires, and data are analysed with t-test statistics. Results: Based on the T-test, there was a significant influence on respondents' level of knowledge and attitudes after being given treatment. The t-test (2-tail) result > 0.05 showed no significant difference between initial and late nutritional status based on HB measurements. This showed no significant effect of treatment with the module of pregnant women on nutritional status. While nutritional status is based on LILA measurements, The T-test results have a significance value (2-tail) < 0.05. This shows that there is a significant effect of intervention on nutritional status after being given treatment Conclusion: The nutrition education-based module for pregnant women has a significant effect on the level of knowledge and attitudes of respondents. There was an increase in knowledge, attitudes, and nutritional status of respondents after nutrition education. It is hoped that pregnant women, after nutrition education, can understand more about Balanced Nutrition and stunting prevention during pregnancy and after childbirth. They are processing the daily food menu with healthy and nutritious food ingredients so that chronic lack of energy and anaemia do not occur during pregnancy.